Hargailah Temanmu : Berikan Senyum Terindah - Dini Asyifa Sari; Najwa Qurrata’Ayun; Siti Eka Pratiwi; Siti Noormala; Rezki Akbar Norrahman (PT. Sharia Journal and Education Center, 2024)
Bullying prevention in early childhood is a crucial aspect of creating a safe and supportive environment for children's development. Bullying can have a negative impact on children's mental and physical health and affect their academic performance. This study examines various prevention strategies that can be implemented in school and family settings, such as social-emotional education, raising parental awareness, and community involvement. The methods used include surveys, interviews, policy analysis and Focus Group Discussions (FGDs). Results show that education programs that involve children, parents and educators collaboratively can reduce the incidence of bullying. In addition, a holistic approach in educating children about empathy and effective communication is proven to be effective in building positive social relationships. The findings suggest the need for sustainable implementation of policies that support bullying prevention to create a safe atmosphere for all children.